Soil physical properties of a fertile, poorly drained soil and their adequacy for use in quantified land evaluation - Mantell, S.; CATIE – Centro Agronómico Tropical de Investigación y Enseñanza, Turrialba, Costa Rica. Atlantic Zone Programme; Agricultural University Wageningen, Wageningen (Países Bajos); Ministerio de Agricultura y Ganadería (MAG), San José (Costa Rica). (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
33 páginas y 104 páginas de Apéndices